A influência da Indústria 4.0 na manutenção e arrecadação da Suframa - Simulação de Monte Carlo - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The Manaus Free Trade Zone Superintendence (SUFRAMA) has an important role in the Western Amazon region and in the state of Amapá. Its objective is to promote regional development. The institution manages and controls the tax incentives granted to companies headquartered within its area of operation. Industry 4.0 (I4.0) is already present all over the world, bringing new technologies to improve large-scale production. Several of these technologies have direct consequences such as the reduction of unskilled human labor, raises concern about the sustainability of the model because SUFRAMA has, in its genesis, financial self-sufficiency arising from fees charged for the services performed. In addition to these, a possible loss of competitiveness of the Industrial Pole of Manaus - PIM also creates an alert that needs to be analyzed. The present study presents scenarios proposed through Monte Carlo simulation, based on historical data from the PIM to evaluate the repercussions of these scenarios, considering the implementation of I4.0 technologies in the main companies of the Industrial Pole of Manaus - PIM and evaluating the behavior of the main factors that impact the model, such as the exchange rate variation, the volume of exports and the import of inputs. The application of the computational tool proved to be efficient to evaluate the impacts of these factors on the results obtained by the PIM and proved to be a capable exercise for evaluating the future of the model.
The influence of Industry 4.0 on the maintenance and collection of Suframa - Monte Carlo Simulation
Keywords: Portos e zonas francas - Manaus (AM); Distritos industriais - Amazônia; Simulação (Computadores); Inovações tecnológicas - Aspectos econômicos; ENGENHARIAS: ENGENHARIA DE PRODUCAO: PESQUISA OPERACIONAL: PROCESSOS ESTOCASTICOS E TEORIAS DA FILAS; Influência; Indústria 4.0; Suframa; Simulação Monte Carlo